Revitalization of SPS Tunas Bangsa PAUD: Creating a Conducive Early Childhood Education Environment - Andika, Andika; Januardi Neo Adi Nugroho; Yessiana Aisyah; Odilia Viola Putri; Allan Frendly Mandala; Rakha Zainda; Felisa Candradewi; Dhea Fitria Handayani; Eden Yudha Permana; Danang Wahyu Prasetyo; Lodewik Rananmase; Zaky Abad Hakim; Handoko Arwi Hasthoro (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to evaluate the effects of the revitalization program on improving the quality of the learning environment at PAUD SPS Tunas Bangsa. Given the importance of a conducive learning environment to spur students' motivation, enthusiasm and curiosity, this study is of particular relevance. Evaluation results showed a significant increase in students' motivation and enthusiasm for learning, supported by positive feedback from teachers and parents. Thus, the program succeeded in creating a more supportive learning environment in PAUD. Based on these results, it is recommended to continue the revitalization by adding educational murals on the school walls and conducting classroom arrangements to support more effective learning activities.